The role of plant-based diet in prostate cancer – a review of literature - Janiszewska, Michalina; Imbirska, Beata; Prager-Zimny, Marta; Cyrulik, Michalina; Ramlau, Natalia; Kolenda, Dominika; Fischer, Zuzanna; Podolak, Marcin; Hładki, Michał; Simachi, Michalina (Journal of Education, Health and Sport, 2025)
Introduction: Connection between plant-based diet and prostate cancer risk is an emerging topic in the scientific field. Diets high in animal products have been associated with increased prostate cancer incidence and mortality. Prostate cancer is among the most common cancers in men, and diet is considered a modifiable risk factor that may influence disease development and progression. Emerging evidence suggests that plant-based diets may reduce prostate cancer risk and improve patient outcomes. Aim of the Study: This review aims to explore the relationship between a plant-based diet and the risk of developing prostate cancer. It focuses on evaluating existing clinical evidence regarding the potential protective effects of plant-based nutritional patterns. We also aim to highlight how dietary choices may contribute to prostate cancer prevention and the importance of connections between nutrition and cancerogenesis. Materials and Methods: We conducted a comprehensive literature review by searching multiple databases, including PubMed, Web of Science and Google Scholar using key terms such as “plant-based diet”, “prostatic neoplasms”, “nutrition”, “prostate-specific antigen”, “lifestyle”, “meat”. Our analysis focused on clinical trials, preclinical studies, and peer-reviewed research relevant to the topic. The selected studies provided a broad overview of current scientific findings. This approach ensured a thorough and up-to-date evidence base for our review. Conclusions: Prostate cancer is one of the most common malignancies affecting men worldwide. Understanding and addressing modifiable risk factors is essential for prevention and improved outcomes. Lifestyle choices, including diet, play a significant role in influencing disease risk. Growing evidence suggests that a plant-based diet may be associated with a reduced risk of developing prostate cancer. It’s important to research modifiable risk factors and to educate patients on their lifestyle choices.